ASPECTS OF LEGAL PROTECTION AGAINST MIDWIFE PROFESSION IN INDONESIA - Hafid Zakariya Hafid (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2022)
The midwife profession in carrying out its practice there are several that are in accordance with their authority, but they always prioritizes the rights of the patient as a form of legal protection in the event of negligence or loss to the patient. The application of Health Seeking Behavior in the relationship between patients as service recipients and midwives as health service providers. Role theory is also included in research on the role of the Health Service and the Indonesian Midwives Association (IMA) as the organizer of government affairs and professional organizations engaged in health, overseeing the implementation carried out by midwives and protecting the midwife profession with a permanent form of legal protection for midwives who make mistakes or loss to the patient, as well as providing legal protection to the patient. Medical actions taken by midwives will be legally enforceable, if the midwife does not carry out the delegation of authority in accordance with statutory regulations. The problem is what is the form of legal protection for the midwife profession in relation to the delegation of authority in carrying out medical actions. this is to examine the form of legal protection, with a normative juridical approach. The delegation of authority for medical action has been regulated in various regulations. The fact is that in daily practice, there are still houses that have not been technically operationally regulated regarding the delegation of authority for medical actions, the mechanism for the delegation of authority, as well as what types of medical actions can be delegated by delegation or mandate states juridically if there is an allegation that the competent authority can file a civil or criminal lawsuit.